The Frequency Characteristic of Silicone Domes in Receiver in the Canal Hearing Aids - Ueno, Masafumi; Shinden, Seiichi; Suzuki, Daisuke; Suzuki, Noriomi; Nishiyama, Takanori; Oishi, Naoki; Ogawa, Kaoru (Journal of the American Academy of Audiology, 2021)
Background There are several types of silicone domes in receiver in the canal hearing aids (RICs), which have different occlusion levels. However, the frequency characteristics of each type of silicone dome are unclear.Purpose This study aimed to determine the frequency characteristics of three types of silicone domes (open domes, double-type power domes, and tulip domes) in RICs.Research Design This is an interventional study.Study Sample In total, 11 participants with a normal sense of hearing were prospectively enrolled.Intervention Participants were fitted with hearing aids, which were adjusted to similar settings, and only the silicone domes were changed. The acoustic gain of hearing aids was adjusted to 20 dB in the range of 250 Hz to 4 kHz using the 2-cc coupler.Data Collection and Analysis We measured the real-ear aided gain (REAG) for each type of silicone dome. In each frequency, we statistically compared the REAG of each type of dome. Acoustic gain using the Open Fit coupler of each type of dome was also measured.Results The REAG was obtained with no leakage with open domes only at 2 kHz, and with tulip domes and double-type power domes in the range of 1 to 2 kHz. Double-type power domes obtained significantly higher REAG than tulip domes at 250 and 500 Hz. Under the Open Fit coupler, all types obtained higher acoustic gain than the REAG.Conclusion This study provides the analysis of the frequency characteristics of silicone domes in RICs. The highest degree of occlusion was observed in double-type power domes, followed by tulip domes, and the lowest was observed in open domes.
Keywords: hearing aid; vent diameter; receiver in the canal; silicone dome; real-ear aided gain